[unknown]
1939-1942: children sanatorium in the Svábhegy, soldiers in Budapest, family at home and in a public park, vacation in Siófok, excursion to Transsylvania (Kolozsvár, Marosvásárhely, Szováta), vacation in the Mátra mountain (Hotel Kékes)